KEWENANGAN YUDISIAL REVIEW MAHKAMAH AGUNG TERHADAP PERATURAN PERUNDANG-UNDANGAN DI BAWAH UNDANG-UNDANG - DONI SILALAHI, SH A.2021131015, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis research raised the issue of judicial authority of the Supreme Court Rules Against Legislation under the Act. This study uses the juridical-normative research. The survey results revealed that the Constitution explicitly states that Indonesia is a country of law (rechtsstaat), not a state based on power alone (machtsstaat). In upholding state law, all products both national and local laws must not conflict with the Constitution, then attempt to correct if there is a legal product that is contrary to the constitution can be completed through a testing mechanism undangan.Namun laws and thus, the dualism testing regulations perundangÂ¬ invitation (judial review) in the Supreme Court and the Constitutional Court is an arrangement that is not ideal, because of potential perdedaan conflicting decisions. In the future, need to be examined any amendment to the Constitution by the events leading to the unification of testing legislation under the roof of the Constitutional Court. Basically the authority of the Constitutional Court as set forth in Article 24C of the 1945 Constitution, is one of them to test the laws of the constitution (Constitution) also there are issues ranging from the process of filling the constitutional judges, some of the Constitutional Court decision was very controversial and raises the pros and cons, acts further on the Constitutional Court decision, until the Constitutional Court Judge supervision issues. Not only in the Constitutional Court, the exercise of judicial review of laws and regulations under the Act against the Constitution in the Supreme Court also has a problem, for example, on the principles of transparency and then obscurity related to the consideration of the judge as the right legal standing in the judicial decision. The problem that arises if left or no effort to get it done, then it will create injustice, lack of legal certainty, and the collapse of public confidence in the Constitutional Court and the Supreme Court. That should have governing authority of the Supreme Court in conducting judicial review of legislation is more efficient in the future is with the idea of a roof in conducting judicial review of legislation. Dogma law put MA and MK, and both can be interchangeable. If the practice of inconsistencies put forward, the Court has a better sociological value. Neither the Supreme Court, the Constitutional Court and the Assembly is an independent state agency, in contrast with the constitutional other countries, like the Netherlands, for example. How the politics of law (law-making) to the front, in place even if there is institutional strengthening of the state, the division of power in accordance with the functions should remain the foundation of the country.Keywords: Authority, Judicial Review, Supreme Court.ABSTRAKPenelitian tesis ini mengangkat masalah kewenangan yudisial review Mahkamah Agung Terhadap Peraturan Perundang-Undangan di bawah Undang-Undang. Penelitian ini menggunakan metode penelitian yuridis-normatif. Dari hasil penelitian diketahui bahwa Konstitusi secara tegas menyatakan bahwa Indonesia adalah negara hukum (rechtsstaat), bukan negara yang berdasar atas kekuasaan belaka (machtsstaat). Dalam menegakkan negara hukum, maka segala produk hukum baik pusat maupun daerah tidak boleh bertentangan dengan konstitusi, maka upaya untuk mengoreksi jika ada produk hukum yang bertentangan dengan konstitusi dapat diselesaikan melalui mekanisme pengujian peraturan perundang-undangan.Namun demikian, adanya dualisme pengujian peraturan perundangundangan (judial review) di Mahkamah Agung dan Mahkamah Konstitusi merupakan pengaturan yang tidak ideal, karena berpotensi menimbulkan perdedaan atas putusan yang saling bertentangan. Kedepan, perlu dikaji adanya amandemen UUD dengan megatur mengenai penyatuan pengujian peraturan perundang-undangan satu atap dibawah Mahkamah Konstitusi. Pada dasarnya wewenang Mahkamah Konstitusi sebagaimana diatur dalam Pasal 24C UUD 1945, yaitu salah satunya menguji undang-undang terhadap konstitusi (UUD) juga masih terdapat persoalan mulai dari proses pengisian hakim konstitusi, beberapa putusan Mahkamah Konstitusi yang sangat kontroversial dan menimbulkan pro-kontra, tindak lanjut atas putusan Mahkamah Konstitusi, hingga permasalahan pengawasan Hakim Mahkamah Konstitusi. Tidak hanya di Mahkamah Konstitusi, pelaksanaan hak uji materiil peraturan perundang-undangan dibawah Undang-Undang terhadap Undang-Undang di Mahkamah Agung juga memiliki permasalahan, misalnya terkait prinsip transparansi kemudian ketidak jelasan terkait dasar pertimbangan hakim tentang legal standing dalam putusan hak uji materiil. Permasalahan yang muncul tersebut jika dibiarkan atau tidak ada upaya untuk menyelesaikannya, maka akan menciptakan ketidakadilan, tidak adanya kepastian hukum, dan runtuhnya kepercayaan publik terhadap Mahkamah Konstitusi dan Mahkamah Agung. Bahwa Seharusnya pengaturan kewenangan Mahkamah Agung dalam melakukan yudisial review terhadap perundang-undangan yang lebih efisien kedepan adalah dengan gagasan satu atap dalam melakukan yudisial review terhadap perundang-undangan. Dogma hukum menempatkan MA dan MK, dan keduanya bisa saling menggantikan. Jika praktik inkonsistensi dikedepankan, maka MK memiliki nilai sosiologis yang lebih baik. Baik MA, MK dan MPR adalah lembaga negara yang berdiri sendiri, berbeda dengan ketatanegaraan negara lain, seperti Belanda misalnya. Bagaimana politik hukum (pembentukan hukum) ke depan, pada tempatnya kalaupun ada penguatan kelembagaan negara, maka pembagian kekuasaan sesuai dengan fungsinya harus tetap menjadi pijakan negara.Kata Kunci : Kewenangan, Yudisial Review, Mahkamah Agung .